Point-of-Care Diagnostic Tools for Surveillance of SARS-CoV-2 Infections - Sakthivel, Dhanasekaran; Delgado-Diaz, David; McArthur, Laura; Hopper, William; Richards, Jack S.; Narh, Charles A. (Frontiers in Public Health, 2021)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is a recently emerged and highly contagious virus that causes coronavirus disease 2019 (COVID-19). As of August 24, 2021, there were more than 212 million confirmed COVID-19 cases and nearly 4.4 million deaths reported globally. Early diagnosis and isolation of infected individuals remains one of the most effective public health interventions to control SARS-CoV-2 spread and for effective clinical management of COVID-19 cases. Currently, SARS-CoV-2 infection is diagnosed presumptively based on clinical symptoms and confirmed by detecting the viral RNA in respiratory samples using reverse transcription polymerase chain reaction (RT-PCR). Standard RT-PCR protocols are time consuming, expensive, and technically demanding, which makes them a poor choice for large scale and point-of-care screening in resource-poor settings. Recently developed isothermal nucleic acid amplification tests (iNAAT), antigen and/or serological tests are cost-effective to scale COVID-19 testing at the point-of-care (PoC) and for surveillance activities. This review discusses the development of rapid PoC molecular tools for the detection and surveillance of SARS-CoV-2 infections.